Cochlear Implants for Children with Residual Hearing: Supporting Family Decision-making - Na, Eunjung (Université d'Ottawa / University of Ottawa, 2021)
Children with residual hearing have become eligible for consideration as CI candidates in some pediatric programs because of the positive clinical research outcomes of cochlear implant (CI). However, decision-making about CIs for children with residual hearing is difficult for parents because they experience uncertainty when their children show auditory benefits and are developing language through hearing aids (HAs). Clinicians may be uncomfortable recommending CI for these children due to variability in audiometric candidacy criteria in individual clinical practice. However, there is very limited information about the CI decision-making process and needs to assist the parents of these children and practitioners. We conducted a comprehensive study to better understand and support the CI decision-making experiences of families and practitioners. The objectives of our study were to: 1) explore the clinical characteristics and outcomes of children with residual hearing who received CIs, 2) summarize the evidence about the benefits and risks of CIs compared to HAs in children with residual hearing, and 3) explore the decision-making process and needs for children with residual hearing from the perspective of parents and practitioners. This research project combined quantitative and qualitative research designs. A retrospective chart review was conducted to address the first objective. Data on the clinical characteristics of children with residual hearing were extracted from medical charts from a tertiary care pediatric CI center in Ottawa, Canada. A systematic review was performed on the benefits and risks of CIs versus HAs for children with residual hearing to address the second objective. The third objective was addressed through two sub-studies. The first sub-study involved qualitative semi-structured interviews. A total of 12 parents participated in individual interviews. In the second sub-study, 17 practitioners at a pediatric CI center in Ottawa, Canada, and specialized teachers of the deaf and hard of hearing at local school boards were recruited, and four focus groups and one individual interview were conducted. This study showed that a total of 100 of 389 (25.7%) children who received CIs from 1992 to 2018 at the Children's Hospital of Eastern Ontario (CHEO) had residual hearing, representing more than half the children who were implanted in the last two years covered by the study. As documented in our study, overall, children with residual hearing demonstrated benefits in auditory functioning following cochlear implantation. Approximately 70% of these children achieved open-set word perception scores of 80% or more post-CI. In the systematic reviews, a total of 3265 citations were identified, of which eight studies met inclusion criteria. The articles consisted of four moderate and two weak quality pre-post cohort studies and two weak quality cross-sectional studies. The systematic review confirmed that children with CIs showed significantly better speech perception scores than those with HAs. Limited evidence of improvement in auditory performance and non-significant improvement in speech intelligibility was found. Two aspects of social-emotional functioning (hyperactivity/inattention and pro-social behaviour) showed significant improvement with CIs. Our finding also contributes new information about the loss of residual hearing and device use. Four studies provided data on risks following CIs; a total of 16 of 43 (37.2%) children showed loss of residual hearing and 14.0% (8/57) of children had discontinued or limited use of their CI or HA. The qualitative interviews revealed that both parents and practitioners identified child’s everyday functioning as an important factor that influenced their decision-making. It was clear through the qualitative research with parents that they held a strong preference for child’s inclusion into hearing society. Spoken communication was a core value for the parents of these children and some parents expressed high expectations that their children’s hearing would become ‘normal’. We found that practitioners primarily supported parental decision-making by providing information on the practical aspects of the benefits and risks of CIs. Overall parents were satisfied with the decision-making process and decision support from practitioners. However, parents stressed the importance of receiving more personalized information that considered their specific concerns, values and preferences related to their child and family’s circumstances. Practitioners also noted that more research among children with residual hearing is needed to guide parental CI decision-making. To our knowledge, the findings from this dissertation are the first to examine decision-making for children with residual hearing. Our study contributes new information about the characteristics of children receiving CIs, the potential benefits and risks for children with residual hearing, and decision-making needs from the perspectives of families and practitioners. In addition, our research is a useful first step in understanding what families need to make better decisions to assist in the CI decision-making process for this specific population.
Keywords: cochlear implant; decision-making; residual hearing; candidacy criteria; decision support; pediatric